A new device for selective mechanical broadleaf weed control in turfgrass. Issue 1 (22nd March 2021) - Henderson, Jason J.
Abstract: Weed control in turfgrass systems without herbicides can be challenging. Cost effective and reliable weed control options are needed in turfgrass systems managed organically or pesticide‐free. The objectives of this research were to determine i) the efficacy of selective, mechanical broadleaf weed control and ii) assess Weedbine injury potential in Poa pratensis L. (Kentucky bluegrass). This study was arranged in a randomized completed block design with two replications. The three treatments were: 1) Weedbine 1X wk –1, 2) synthetic herbicide, and 3) mow only control. Synthetic herbicides provided the quickest and most definitive level of weed control. However, the Weedbine used once per week immediately prior to mowing provided significantly higher weed control compared to the mow only control consistently throughout the growing season. Mechanically treated plots exhibited some turfgrass injury following treatments in August and September. However, mechanically treated plots had higher turfgrass quality than herbicide‐treated plots in November due to subsequent weed encroachment in herbicide treated plots later in the growing season. The Weedbine has potential for applying selective, mechanical weed control with minimal injury in Poa pratensis .